Need-based remote exercise management platform for colorectal cancer patients with intestinal stoma: design and pilot usability evaluation - Yao, Cui; Ding, Lingyu; Yang, Jing; Sun, Yueming (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveTo develop and evaluate the usability of a comprehensive remote management platform specifically designed to promote exercise among colorectal cancer patients with intestinal stomas.MethodsWe employed a multifaceted approach to platform development, integrating systematic literature reviews, semi-structured patient interviews, healthcare provider consultations, and interdisciplinary expert panel discussions to identify the unique exercise management needs of colorectal cancer patients with intestinal stomas. Based on these comprehensive needs assessments, we constructed a specialized remote exercise management platform. Platform usability was subsequently evaluated using the validated System Usability Scale (SUS).ResultsThe finalized platform architecture comprised two interconnected interfaces: a patient-centered portal and a healthcare provider administrative system. Usability evaluation was completed by 62 colorectal cancer patients with intestinal stomas, yielding a mean SUS score of 88.39 ± 3.65, substantially exceeding benchmark standards for digital healthcare applications.ConclusionThe developed platform demonstrates exceptional usability while offering comprehensive functionality, evidence-based content with rigorous medical validation, and robust security features. This technological solution provides a practical framework for enhancing exercise management quality in colorectal cancer patients with intestinal stomas and establishes a blueprint for similar applications addressing postoperative rehabilitation needs in other clinical populations.